АНАЛІЗ ПОШИРЕНОСТІ ПОСТТРАВМАТИЧНОГО СТРЕСОВОГО РОЗЛАДУ СЕРЕД МЕДИКІВ У ЗОНІ БОЙОВИХ ДІЙ - Нікон, Наталія (SWorldJournal, 2025)
The article presents the results of an empirical study devoted to examining the prevalence of post-traumatic stress disorder (PTSD) among military medical personnel performing their professional duties in combat conditions. The relevance of the problem is